The Analysis of Deixis on “Closed Doors” Song - Khanna Maulidia 'Ashr; Rawuh Yuda Yuwana (Musamus Journal of Language and Literature, 2023)
In this research, the author focuses on a pragmatic approach to the study of deixis analysis in the song "Closed Doors" by Ismail. The aim of this research is to describe the types found in song lyrics and explain the meaning of the deixis used. The method used is a qualitative descriptive method. The data taken comes from all the lyrics of the song Closed Doors. From this song, researchers obtained 34 data of person deixis, 8 spatial deixis data, and 4 temporal deixis data. Person deixis is most dominant in the song's lyrics compared to other types of deixis. The meaning of the song refers to the perspective of the singer and listener of the song, the people in the song, the time of an event or action, and the particular place where certain things or feelings discussed in the song Closed Doors occur.